A new solifugae species of Mummucina Roewer, 1934 (Solifugae, Mummuciidae) from the Northwest of Argentina - Reyes, González; Ximena, Andrea; Corronca, José Antonio (Zootaxa, 2013)
A new species of Mummuciidae, Mummucina puna sp. nov. (male and female) from Northwest Puna eco-region of Salta province, Argentina, is described and illustrated. A key and distribution map of known species of the genus Mummucina are provided.